Brand Image and Service Quality on Product Purchasing Decisions - Fitriany Fitriany (Jurnal Economic Resource, 2022)
This study aims to examine and analyze the effect of brand image and service quality on purchasing decisions for wardah products (Case study on female students 2018-2020 Nobel Indonesian Institute of Technology and Business. Data was collected by distributing questionnaires and a population of 1,484 female students 2018-2020 Institute of Technology and Nobel Business Indonesia. At the same time, the determination of the sample used the slovin formula with the results of as many as 94 respondents who will be distributed questionnaires. Data is sourced from primary data and secondary data. Primary data from this study were obtained from questionnaires filled in by users of wardah cosmetics, including identity and responses according to the results of filling out the questionnaire. Secondary data, among others, are presented as data, documents, and tables regarding the topic. Secondary data used in this study is in the form of literature studies, journals, literature relating to problems, and information about image data brand d and service quality on purchasing decisions at wardah cosmetic stores. The results of the analysis show that the brand image variable has a significant and significant effect on purchasing decisions with a significant value of 0.007 <0.05, and service quality has a positive and significant effect on purchasing decisions with a significant value of 0.000 <0.05.